Emotional Abuse dan Self-Esteem Remaja dalam Perspektif Al-Qur’an: Kajian Tafsir QS. Luqman [31]:13 - Fayi Risma Mufidah; Amir Mahmud; Wiwin Ainis Rohtih; Miftara Ainul Mufid (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study examines emotional abuse toward adolescents from the perspective of Qur’anic interpretation, particularly through QS. Luqman [31]:13, as an effort to understand the relationship between parenting patterns and the formation of adolescent self-esteem. Emotional abuse, such as verbal humiliation, intimidation, emotional neglect, and excessive criticism, often occurs unconsciously within family environments and contributes significantly to psychological disturbances among adolescents. Employing a qualitative approach based on library research and thematic interpretation (tafsīr maudhū‘ī), this study analyzes Qur’anic values related to communication ethics, emotional protection, and the preservation of human dignity. The findings reveal that QS. Luqman [31]:13 presents a compassionate educational communication model through the expression yā bunayya, reflecting affection, emotional validation, and persuasive parenting. The Qur’an positions children as dignified human beings whose psychological well-being must be protected from destructive verbal and emotional treatment. This study argues that Qur’anic educational values provide preventive principles against emotional abuse by promoting empathy, respectful communication, and emotional security within the family. Theoretically, this research contributes to the development of Islamic psychology and Qur’anic parenting studies by positioning the Qur’an as a foundational framework for adolescent mental well-being and healthy self-esteem formation.